International Military Education and Training: Promoting Democratic Values to Militaries and Countries throughout the World. Issue 3 (3rd July 2019) - Mujkic, Edin; Asencio, Hugo D.; Byrne, Theodore
ABSTRACT: The International Military Education and Training program is the United States security assistance program that provides professional military education to officers from foreign militaries. As a tool of soft power, the program has the potential of helping the United States achieve its foreign and national security goals. Despite the potential benefits of the program, research on its effectiveness is limited. The present study contributes to the literature by inquiring into what benefits toward acquiring an understanding of democratic values and the United States society are expressed by foreign officers who have participated in the program.